ENHANCING ENGLISH PROFICIENCY: THE IMPACT OF COMMUNICATIVE LANGUAGE TEACHING ON SECOND LANGUAGE LEARNERS - Febri Dhany Triwibowo (Tomorrow's Education Journal, 2023)
This research investigates the effectiveness of Communicative Language Teaching (CLT) in enhancing English language proficiency among second language learners. Using a qualitative approach, the study explores learner engagement, cultural awareness, and the role of teachers in CLT. Participants held positive perceptions of CLT, which facilitated real-life language practice and boosted their confidence. Improved English proficiency, especially in speaking, listening, and interactive skills, resulted from the learner-centred and practical nature of CLT. The research emphasizes the importance of integrating CLT techniques into language teaching and underscores the need for well-designed teacher training programs to optimize CLT's benefits in diverse language learning contexts. This study aims to inform educators and policymakers in developing efficient and learner-centred language programs to meet the demand for English proficiency in an interconnected world.